Brazilian organic sugarcane spirits: physicochemical and chromatographic profile - Duarte, Felipe; Cardoso, Maria das; Santiago, Wilder; Machado, Ana Maria; Nelson, David (Revista Ciência Agronômica, 2016)
There has been a growing demand for products from organic agriculture for the food market. Brazil leads the production of sugarcane spirits and produces about 1.6 billion liters/year. New technologies have been sought throughout the supply chain to improve production, and organic raw material has been used in the production of sugar cane for the production of beverages. This study aimed to define the physicochemical and chromatographic profiles of eleven organic sugarcane spirits samples from various Brazilian states. The secondary components and contaminants were identified and quantified through physicochemical analyses, HPLC and gas chromatography (GC). A significant percentage of the organic sugarcane spirits samples contained concentrations of components that were above the limits required by the Ministry of Agriculture, Livestock and Provisioning (MAPA), specifically the esters (18.20%), copper and dry extract (9.10%). This contamination is caused by bad conditions employed during the production process, which are not in compliance with the good manufacturing practices determined and legislated by Brazilian law.